Tax Evasion and its Control in Nepalese Context - Neupane , Bharat (Journal of Deukhuri Multiple Campus, 2026)
Nepal’s public revenue is obtained through taxation, which has assumed an important role in the government contributing to various types of public good and investment on infrastructure and social welfare. Even though a succession of tax system and administration reforms have been carried out, the problem of noncompliance has persisted with detrimental effects on revenue generation as well as on long run fiscal sustainability. The weaknesses with the system despite its structural improvement are weak enforcement mechanisms, administrative lacunae, cumbersome tax procedures and poor technology usage along with increased refusal among taxpayers to repose faith in public institutions. Against this background, in this study we try to investigate the antecedents of tax evasion in Nepal and its containment purpose. It also explores alternative approaches that might be more practicable and applicable for improving compliance by way of similarly improved tax performance. Based on the extant theoretical and empirical literature, official government documents, and evidences from international comparative case studies of tax evasion in this article provides authorities in Nepal with a range of instruments that might be effective in dealing with problems of tax evasion. The strategy is based on a well-balanced three-pronged programmer encompassing more rigorous enforcement, simplification of the tax system and greater digitization of tax administration as well as better information education communication for taxpayers. Room is also created to address administrative incompetence and behavioural handicaps in getting people to conform, a piece of political chapter on fairness and transparency with respect to the spending of public money. Closing administrative loopholes and synchronizing the incentives for voluntary compliance, can produce significant improvements in revenue performance, the study argues. Ultimately, by building an efficient and transparent tax system that is also easily comprehended and accepted by citizens, Nepal may be better placed to develop and sustain inclusive and sustainable economic development. Tax is a foundation of nation building but there is massive tax gap because of the enormous scale of tax evasion in Nepal. This paper examines structural origins of tax evasion in Nepal, combining administrative and socio-economic perspectives.